BIOPHOTONS IN RADIOBIOLOGY: INHIBITORS, COMMUNICATORS AND REACTORS. Issue 1 (9th January 2019) - Mothersill, Carmel; Le, Michelle; Rusin, Andrej; Seymour, Colin
Abstract: Radiation-induced bystander effects refer to the production of signals from irradiated cells which induce responses in unirradiated, or bystander, cells. There has been a recent resurgence of interest in low-energy photon biology. This is due to concerns about health effects, increased use of biophoton imaging techniques, and the fact that biophotons can act as a bystander signal. This review discusses the history of light signaling in biology and potential mechanisms involved in the generation and transduction of signaling mechanisms. The role of photons in signaling in the animal and plant kingdoms is also reviewed. Finally, the potential to harness these mechanisms in radiation protection or therapy is discussed with emphasis on promising future directions for research.